Biosynthesis of Gold Nanoparticles using Fig Leaf (Ficus Carica) Isolate as a Reducing Agent - Lusiana, Nova; Ma'arif, Muhammad; Agustina, Eva; Purnamasari, Risa (Journal of Health Science and Prevention, 2024)
Proper and swift treatment is crucial for cancer patients. The fig plant contains antioxidants that show inhibition of cancer cell proliferation. By converting its particle size into nano, the active compounds are expected to more easily reach the target cells. The aim of this study is to determine the effectiveness of gold nanoparticles with a reducing agent from fig leaf isolate (Ficus carica). The research method used is laboratory experimentation to produce gold nanoparticles with fig leaf extract as the reducing agent, and the antioxidant activity was tested by observing the IC50 value. The results of the study showed that gold nanoparticles from fig leaf extract were successfully created, as evidenced by UV-Vis spectrophotometer testing at a wavelength of 528 nm. The antioxidant test demonstrated that gold nanoparticles from fig leaf extract have greater potential as an antioxidant agent compared to fig leaf extract alone.